THE ROLE OF PROSECUTOR OFFICE IN THE ERADICATION OF CORRUPTION CRIMINAL ACTS IN INDONESIA - Sri Endah Wahyuningsih; Agus Sunaryo (Jurnal Pembaharuan Hukum, 2017)
In fact, there are still many cases of corruption that have not been revealed; this resulted in the public to be pessimistic with the seriousness of the Prosecutor Office in uncovering variouscases of corruption that are happening today. The purpose of this study is to know the role ofthe Prosecutor Office in the eradication of criminal acts, to obtain an overview of the mechanismof corruption handling by prosecutors in Indonesia and to analyze the obstacles and solutionsin eradicating crime in the Attorney General. The research method was sociological juridical,and data collection were gained by using observation and interview. The existence and role ofthe Public Prosecution Service in eradicating corruption crime begins when the case has notbeen transferred to the Court until the execution of the decision of the Court. However, in thecriminal act of corruption the Prosecutor’s Office has the authority as a public prosecutor aswell as an investigator. The authority of the prosecutor as a special criminal investigator shall beregulated by Law Number 16 Year 2004 regarding the Attorney of the Republic of Indonesia inArticle 30 paragraph (1) letter d. In addition, in its role against the eradication of corruption, theProsecutor’s Office has always conducted a coordination relationship with the Police Agency andthe Corruption Eradication Commission. The mechanism for handling corruption in the AttorneyGeneral Office, through several procedures already set out in the law includes Investigation,Investigation and Prosecution.